Healthcare-Associated Infections and Shanghai Clinicians: A Multicenter Cross-Sectional Study - Zhou, Yunfang; Zhang, Dangui; Chen, Youting; Zhou, Sha; Pan, Shuhua; Huang, Yuanchun; Ba-Thein, William (PLOS ONE, 2014)
Literature about healthcare-associated infection (HCAI) in China is scarce. A cross-sectional anonymous survey was conducted on 647 clinicians (199 physicians and 448 nurses) from six Shanghai hospitals (grades A–C) to investigate their cognizance, knowledge, attitude, self-reported practice, and risks regarding HCAI with emphasis on precautions. The mean overall score of HCAI knowledge was 40.89±11.4 (mean±SD; range, 13∼72) out of 100 for physicians and 43.48±9.9 (10∼70) for nurses. The respondents generally received high scores in hand hygiene, HCAI core concept, and healthcare worker safety but low scores in HCAI pathogen identification and isolation precautions. There were substantial variations in the knowledge scores of various demographic groups across individual hospitals and within hospital grades (ps<0.05). Within-hospital comparisons showed that the nurses were better than physicians particularly in hand hygiene knowledge in 4 hospitals (ps<0.05). Multiple linear regression analysis showed that longer work experience was inversely and independently associated with the overall and categorical knowledge of nurses, whereas independent associations between older age or higher education and categorical knowledge were noted for physicians. The respondents' self-reported practices and adherence to standard precautions were less than satisfactory. This multi-center study reports a high level of cognizance, patchy knowledge, suboptimal adherence to infection control precautions, and self-protective attitudes among the practicing clinicians regarding HCAI, with potential safety risk to patients and healthcare providers. Providing quality learning resources, enforcing knowledge-informed practice, and promoting a healthcare safety culture are recommended as interventions. Future studies are warranted for social and behavioral aspects of healthcare safety with emphasis on infection control.